Repercussions of teenage pregnancy in the life of adult women - Patrícia Mattos Monteiro Dias; Jocélia Maria de Oliveira; Amanda Peres Lustosa; Hana Klébia Leonel da Silva Lima; Karla de Abreu Peixoto Moreira; Thayza Miranda Pereira (Universidade Federal do Ceará, 2017)
To uncover the repercussions of pregnancy during adolescence on the life of women in adulthood. Methods: a qualitative study performed in a Basic Health Unit. Individual data were collected and recorded with seven women for data collection. For the organization of the data, the Thematic Categories Analysis was adopted. Results: three categories emerged: recalling the experiences of pregnancy in adolescence, positive and negative repercussions of teenage pregnancy in the view of women and rescuing knowledge about contraceptive methods in adolescence. Conclusion: the pregnancy occurred in adolescence had positive repercussions when reporting the development of responsibility and maturity, the constitution of a family, and being a mother. As for the negative aspects, the following were observed: the non-completion of the studies; fear of having another child; responsibility; difficulty in reaching plans for the future.